Cost-effectiveness of surgical treatment for hip fractures among the elderly in Brazil - Fabiano Bolpato Loures; Alfredo Chaoubah; Vinícius Silveira Maciel; Elenir Pereira Paiva; Patrick Pereira Salgado; Álvaro Correa Netto (Revista Brasileira de Ortopedia, 2015)
OBJECTIVES: To estimate the cost per quality-adjusted life-year (QALY) focusing on the length of time between trauma and surgery.METHODS: A retrospective cohort with systematic sampling was conducted among all the patients who were admitted to the study hospital through the Brazilian National Health System (SUS) over a three-year period. Two treatment strategies were compared: early treatment, if the patient was operated up to the fourth day; and late treatment, if this was done after the fourth day. The cost was the direct medical cost from the point of view of SUS, which was gathered from the management system, from the SUS table of procedures, medications and implant material costs (SIGTAP), to account for the costs associated with the hospital, medical fees and implants used. The outcome of usefulness was measured indirectly by means of EuroQOL-5D, which is an instrument used worldwide, and these measurements were transformed into usefulness by means of the standard rules of the Regional Planning and Development Center of Minas Gerais (CEDEPLAR) of 2013.RESULTS: The sample included 110 patients: 27 in the early group and 83 in the late group. The confounding variables of age, gender, anesthetic risk (ASA), fracture type and surgery type were controlled for. The samples were shown to be homogenous with regard to these variables. The cost per QALY of the early strategy was R$ 5,129.42 and the cost of the late strategy was R$ 8,444.50.CONCLUSION: The early strategy was highly favorable in relation to the late strategy in this study.